El conflicto socioambiental de Xstrata en Espinar en el periodismo online - Bernuy Chavez Arroyo, Fernando (2023)
This research analyzes from a retrospective perspective the information coverage of the socio-environmental conflict in the province of Espinar in Cusco, developed by the digital press that influenced more than the country for a year, between May 2012 and April 2013 an important player in this conflict began its operations in 1985 as a state company and soon after confronted the claim of the Espinar community that rejected the expropriation of the lands they occupied in order to be the object mining exploitation. Since then, a conflictive relationship was established especially when the project passed into the hands of the private sector (The Company Xstrata), accused of contaminating the environment and neglecting the social agenda of the population. The main question of the investigation is: What was the theme that the capital´s online press made about the conflict in Espinar? Based on the agenda-setting and framing theories, and a mixed methodology, the study identifies the most discussed issues, the most consulted actors and the dominant approaches or frames. It is found that for the press the first person responsible is the government, for not establishing channels of dialogue between the mining company and the population, and for renouncing its supervisory role of extractive activities in the country. Although the analyzed media focused on the conflict from their respective editorial lines, in some cases they assumed critical positions towards actors that they could possibly have defended, such as the communities located in the zone of interference by mining company. Thus, the analysis confirms that the most frequent framework is related to dialogue and violence; Secondly, it highlights the attribution of responsibility.